Stress Management Training for Working, Elderly, and Health Cadre Women : Rumah Pendamping Emak Sehat Jiwa - Kellyana Irawati; Arif Wahyu Setyo Budi; Fahni Haris (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Emotional mental disturbances occur more often in adult women due to the influence of the estrogen hormone. Working women tend to have more burdens than women who do not work. Mental emotional disturbance in women, such as stress and anxiety, can interfere with their productivity and lead to depression. The aim of this social empowerment is to do mental health screening and management stress training i.e. deep breathing, the five-finger hypnosis, and progressive muscle relaxation in order to reduce the sign and symptom of stress and anxiety. Mental health screening was conducted using the Self Reporting Questionnaire-20 (SRQ-20). Initially, 44.2% of respondents experienced signs and symptoms of anxiety. After undergoing deep breathing training, the five-finger hypnosis, also progressive muscle relaxation for four meetings in one month, the signs and symptoms of stress and anxiety in women has decreased. The conclusion from this activity is stress management training with deep breathing, the five-finger hypnosis, and progressive muscle relaxation in adult and elderly women can reduce stress and anxiety levels.